Doing philosophy: Beyond books and classrooms - Kaz Bland; Rob Wilson (Journal of Philosophy in Schools, 2023)
‘Philosophy in community’ projects provide powerful, immersive introductions to philosophical thinking for both children and tertiary students. Such introductions can jumpstart transformative learning as well as diversify who seeks out philosophy in the longer term, both in schools and in universities. Using survey responses from teachers, parents, participants, staff, and volunteers of two such programs—Eurekamp Oz! and Philosothon—we show how participants find value in engaging in communities of inquiry and philosophical thinking more broadly. We argue correspondingly that such philosophy in community projects are an asset to universities, both as highly successful university outreach programs and in offering high school, undergraduate, and postgraduate students mentoring and employment opportunities utilising their growing philosophical skills. For these reasons, philosophy in community programs provide alternative and supplementary pathways into sustained philosophical thinking to those available within traditional philosophy in the classroom approaches.